Swimmers` experiences of organizational stress: Exploring the role of cognitive appraisal and coping strategies - Pineau, T. R.; Glass, C. R.; Kaufman, K. A.; Bernal, D. R. (Journal of Clinical Sport Psychology, 2014)
This study investigated sport performers' coping strategies in response to organizational stressors, examined the utility of Skinner, Edge, Altman, and Sherwood's (2003) categorization of coping within a sport context, determined the short-term perceived effectiveness of the coping strategies used, and explored appraisal-coping associations. Thirteen national standard swimmers completed semistructured, interval-contingent diaries every day for 28 days. Results revealed 78 coping strategies, which supported 10 of Skinner et al.'s (2003) families of coping. Twenty-four different combinations of coping families were identified. The perceived most effective coping family used in isolation was self-reliance and in combination was escape and negotiation. Stressful appraisals were associated with varied coping strategies. The results highlight the complexity of coping and point to the importance of appraisal-coping associations. Skinner et al.'s (2003) categorization of coping provides a promising conceptual framework for the development of coping research in sport. ABSTRACT FROM AUTHOR